Mitigating risk: mediating transition through the enactment of information literacy practices. Issue 5 (27th June 2019) - Hicks, Alison
Abstract : Purpose: The purpose of this paper is to present the emergent grounded theory of mitigating risk, which was produced through an analysis of the information literacy practices of English-speakers who are learning a language overseas as part of their undergraduate degree. Design/methodology/approach: The grounded theory emerges from a qualitative study that was framed by practice theory and transitions theory, and employed constructivist grounded theory, semi-structured interviews and photo-elicitation methods to explore the information activities of 26 language-learners from Australia, Canada, the UK and the USA. Findings: The grounded theory of mitigating risk illustrates how academic, financial and physical risks that are produced through language-learner engagement overseas catalyse the enactment of information literacy practices that enable students to mediate their transition overseas. Research limitations/implications: This study's theory-building is localised and contextual rather than generalisable. Practical implications: The grounded theory broadens librarians' and language-educators' knowledge of student activities during immersive educational experiences as well as extending understanding about the shape that information literacy takes within transition to a new intercultural context. Social implications: The grounded theory develops understanding about the role that local communities play within intercultural transition and how these groups can respond to and prepare for increasingly fluid patterns of global movement. Originality/value: This paper contributes to an increasingly sophisticated theoretical conceptualisation of information literacy while further providing a detailed exploration of transition from an information perspective.